PENCATATAN DATA TRANSAKSI KEUANGAN PADA USAHA MIKRO DAN KECIL: STUDI KASUS DI KAMPUNG ROTI SURABAYA - Setiadi Alim Lim; Galuh Artika Febriyanti (Jurnal Bisnis Terapan, 2017)
Research from Dawuda and Azeko (2015) in Bolgatanga Municipality, Ghana found that 75% of small businesses do not record financial transactions and only 25% have recorded financial transactions. This study aims to examine whether 75% of micro and small enterprises such as the findings of Dawuda and Azeko (2015) do not record financial transaction data. In addition, it will also be examined whether the recording of financial transactions data according to micro and small enterprises is useful or not to measure business performance, the need to apply for credit and tax purposes. The object of research is micro and small business in Kampung Roti, Surabaya. From population of 65 micro and small enterprises in Kampung Roti, Surabaya taken 38 micro and small enterprises as sample. The results showed that 75% of micro and small enterprises did not record financial transaction data. According to 75% of micro and small enterprises recording financial transaction data does not provide benefits to measure business performance, the need to apply for credit and tax purposes. There is a relationship between the decision of micro and small enterprises to do or not to record financial transaction data with measuring business performance, the need to apply for credit and tax purposes.